2018
DOI: 10.1016/j.nbd.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Muscle microRNA signatures as biomarkers of disease progression in amyotrophic lateral sclerosis

Abstract: ALS is a fatal neurodegenerative disorder of motor neurons leading to progressive atrophy and weakness of muscles. Some of the earliest pathophysiological changes occur at the level of skeletal muscle and the neuromuscular junction. We previously identified distinct mRNA patterns, including members of the Smad and TGF-β family, that emerge in muscle tissue at the earliest (pre-clinical) stages. These patterns track disease progression in the mutant SOD1 mouse and are present in human ALS muscle. Because miRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 45 publications
7
38
0
Order By: Relevance
“…At the same time, a significant reduction of this miRNA was present in a specific ALS patients’ group with higher disease severity [ 95 ], suggesting changes in its expression during the disease progression. In contrast, however, other studies detected a down-regulation of miR-133a in human biopsies, as reported also in mice [ 92 , 94 ]. At the moment, the strongest data are those concerning miR-206.…”
Section: Mirnas As Biomarkers For Alsmentioning
confidence: 74%
See 2 more Smart Citations
“…At the same time, a significant reduction of this miRNA was present in a specific ALS patients’ group with higher disease severity [ 95 ], suggesting changes in its expression during the disease progression. In contrast, however, other studies detected a down-regulation of miR-133a in human biopsies, as reported also in mice [ 92 , 94 ]. At the moment, the strongest data are those concerning miR-206.…”
Section: Mirnas As Biomarkers For Alsmentioning
confidence: 74%
“…Most studies focused on the expression of myo-miRNAs [ 90 , 91 , 92 , 93 ]; only in some cases also other miRNAs were included, for example miRNAs related to inflammation/angiogenesis [ 93 ] or selected by microarray [ 72 ] or NGS approaches [ 94 , 95 ]. Overall, results are sometimes contrasting and poorly reproducible.…”
Section: Mirnas As Biomarkers For Alsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we further revealed another feature in the frontal and parietal bone with a distinct miRNA pattern. Small RNA sequencing has been demonstrated to be effective to identify novel miRNAs, and based on this technique, we found that 83 known miRNAs were significantly expressed in frontal versus parietal bone, and about 29 potential novel miRNAs candidates at 18 to 26 nt in length were found. These novel miRNAs are worthy for further functions analysis in osteogenic capacities in Fb versus Pb.…”
Section: Discussionmentioning
confidence: 98%
“…[ 5 ] MiRNAs regulate the level of proteins by regulating levels of mRNAs. [ 16 ] Alterations in the expression profile of miRNAs in Alzheimer's disease (AD) patients,[ 17 ] Parkinson's disease (PD) patients,[ 18 ] amyotrophic lateral sclerosis (ALS) patients,[ 19 ] and Huntington's disease (HD) prodromal patients[ 20 ] illustrate the important role of miRNAs in neurodegenerative diseases. Dysregulation of miRNAs is closely related with AD, PD, HD, and ALS.…”
Section: Introductionmentioning
confidence: 99%